Contingent Valuation of Yangtze Finless Porpoises in Poyang Lake, China - Dong, Yanyan; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
Yangtze Finless Porpoises (YFPs), the only fresh-water adapted porpoises in the world, are endemic to the Yangtze River system, including Poyang Lake. Their population is rapidly decreasing, under threats from illegal fishing and overfishing, dredging, intensive shipping traffic and pollution from agriculture and industry. Since 1996, they have been classified as endangered on the Red List of the International Union for Conservation of Nature. Now a new threat looms, in the form of a Poyang Lake hydroelectricity project being planned by the government of Jiangxi Province. This will cut off their migration route and fragment their habitat. Today, it is more urgent than ever to take measures of protection for YFPs. One possibility for protecting YFPs is a nature reserve located in Poyang Lake. An economic analysis has been conducted to determine whether a nature reserve is worthwhile. Using the contingent valuation approach, the study aims to estimate the benefits of the porpoises by asking individuals$1 (Bwillingness to pay for the porpoise conservation project. The valuation workshop method, a group-based approach which can inform and motivate respondents so that they thoroughly consider the questions, was chosen to help respondents construct their preference. Valuation workshops were successfully organized and data and information were collected. This book presents the findings of the study, and offers analysis of both its methodological and policy-related implications. On the methodology side, it assesses and validates the valuation workshop approach; appraises the effect of distance on willingness to pay and the influence of the respondents$1 (Bability to pay. From a policy perspective, the book examines the attitudes and preference of respondents on trade-offs between economic growth and ecological use. This is the only available study offering economic perspective on Yangtze finless porpoises and the environmentally sensitive Poyang Lake, the largest freshwater lake as well as the last basin of clean water in China.s
1. Introduction -- 1.1 Problem Statement -- 1.2 Goal of the Study -- 1.3 Structure of the Thesis -- 2. Background Information of Poyang Lake and Yangtze Finless Porpoises -- 2.1 Introduction to Poyang Lake -- 2.2 Uses of Poyang Lake -- 2.3 Use Conflicts in Poyang Lake -- 2.4 Yangtze Finless Porpoises -- 2.5 Conclusion -- 3. Theoretical Background on Economic Valuation -- 3.1 Introduction: Reasons for Economic Valuation -- 3.2 Market failure on the Protection of Yangtze Finless Porpoises -- 3.3 Total Economic Value -- 3.4 Economic Valuation Methods -- 3.5 Theoretical Basis of Contingent Valuation Method -- 3.6 Challenges Faced by Contingent Valuation -- 3.7 Conclusion -- 4. Questionnaire Development -- 4.1 Focus Group -- 4.2 Questionnaire Structure -- 4.3 Pre-Test and Modification of Questionnaire -- 4.4 Implementation of the Questionnaire -- 4.5 Survey Method -- 5. Results -- 5.1 Sample Characteristics -- 5.2 Attitudinal Questions -- 5.3 Validity of Responses -- 5.4 Quantitative Analysis -- 5.5 Conclusion -- 6. Discussion -- 6.1 Difficulties with the Design of Contingent Valuation Studies in China -- 6.2 Distance Effect -- 6.3 Different WTP in Germany and China -- 6.4 Summary -- 7. Conclusions -- 7.1 General Conclusions -- 7.2 Recommendations for Future Research -- Appendix A: Demographic characteristics of participants in Focus Groups -- Appendix B: Summary of Focus Group Findings -- Appendix C: Summary of Interviews with Experts -- Appendix D: Questionnaire -- Index.
Keywords: Environmental sciences; Science (General).; Statistics; Economics; Migration; Philosophy (General).; Environment; Environment, general; Economics/Management Science, general; Migration; Science, general; Psychology, general; Statistics, general